2019
DOI: 10.1002/ece3.5797
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of human impacts on endangered red pandas (Ailurus fulgens) living in the Himalaya

Abstract: Anthropogenic factors play an important role in shaping the distribution of wildlife species and their habitats, and understanding the influence of human activities on endangered species can be key to improving conservation efforts as well as the implementation of national strategies for sustainable development. Here, we used species distribution modeling to assess human impacts on the endangered red panda (Ailurus fulgens) in high‐altitude regions of Nepal. We found that the distance to paths (tracks used by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…This demonstrates the importance of bamboos as one of the fundamental parameters affecting red panda distribution (Dorji et al, 2011;Fox et al, 1996;Williams, 2004;Yonzon & Hunter, 1991b). This finding is similar to the findings of Thapa et al (2020), Panthi et al (2019), Thapa et al (2018), Sharma et al (2014), Pradhan et al (2001) and Yonzon & Hunter (1989). Besides bamboo species, other food such as seasonal fruiting berries contribute a very little proportion in food of the red pandas (Yonzon & Hunter, 1991b).…”
Section: Discussion and Con Clus I Onsupporting
confidence: 85%
See 2 more Smart Citations
“…This demonstrates the importance of bamboos as one of the fundamental parameters affecting red panda distribution (Dorji et al, 2011;Fox et al, 1996;Williams, 2004;Yonzon & Hunter, 1991b). This finding is similar to the findings of Thapa et al (2020), Panthi et al (2019), Thapa et al (2018), Sharma et al (2014), Pradhan et al (2001) and Yonzon & Hunter (1989). Besides bamboo species, other food such as seasonal fruiting berries contribute a very little proportion in food of the red pandas (Yonzon & Hunter, 1991b).…”
Section: Discussion and Con Clus I Onsupporting
confidence: 85%
“…This elusive animal frequently uses specific latrine sites for defecation (Yonzon & Hunter, 1989). In Nepal, red panda presence has been documented from 24 districts and seven protected areas with potential habitat of 13,800 km 2 to 24,000 km 2 (Bista et al, 2017;Panthi et al, 2019;Thapa et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In India, the red panda is protected under Schedule-I of the Wildlife (Protection) Act, 1972 and most of its populations reside in small and isolated protected areas (< 500 sq. km), thereby increasing high risk of local extirpation of red pandas due to genetic inbreeding and loss of heterozygosity 15,[17][18][19] . Earlier studies available on red panda from KL-India have addressed population status, distribution, and abundance 11,20,21 , habitat preferences and diet composition 22,23 .…”
mentioning
confidence: 99%
“…Their global population has declined by 50% in the last three generations [ 9 ]. Available studies have reported habitat loss and fragmentation as the major conservation challenges [ 15 , 16 , 17 , 18 , 19 ]. However, most of these studies are based on sign surveys, and they have not attempted to examine how this threatened species responds to habitat loss, fragmentation, and disturbances.…”
Section: Introductionmentioning
confidence: 99%